A reductionist perspective on HIF-1a's role in cell proliferation under non-hypoxic conditions - Dreute, Jan; Pfisterer, Maximilian; Schmitz, M. Lienhard; Justus Liebig University Giessen (My University, 2024)
The role of hypoxia-inducible factor (HIF)-1α in the control of proliferation under non-hypoxic conditions has been investigated in numerous studies, but does not yield a coherent picture. Therefore, we conducted this meta-analysis of existing literature to systematically evaluate the role of HIF-1α, based on a number of inclusion and exclusion criteria. Studies analyzing non-transformed, primary cells showed a largely heterogeneous distribution of pro-proliferative, anti-proliferative or absent functions for HIF-1α, which are co-determined by several parameters, including the type and age of the cell and its localization in tissues and organs. In contrast, the analyses of tumor cells showed a predominantly pro-proliferative role of HIF-1α by cell-intrinsic and cell-extrinsic molecular mechanism not yet understood.
Keywords: ddc:610